2003
DOI: 10.1016/s0093-934x(02)00532-1
|View full text |Cite
|
Sign up to set email alerts
|

On the lateralization of emotional prosody: An event-related functional MR investigation

Abstract: In order to investigate the lateralization of emotional speech we recorded the brain responses to three emotional intonations in two conditions, i.e., ''normal'' speech and ''prosodic'' speech (i.e., speech with no linguistic meaning, but retaining the Ôslow prosodic modulationsÕ of speech). Participants listened to semantically neutral sentences spoken with a positive, neutral, or negative intonation in both conditions and judged how positive, negative, or neutral the intonation was on a five-point scale. Cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
193
2
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 278 publications
(233 citation statements)
references
References 64 publications
32
193
2
6
Order By: Relevance
“…These results together suggest that both the left and the right IFC are involved in the processing of emotional value from voices with no clear laterality effects (Kotz et al, 2003). Summarizing the peak activations across all fMRI and PET studies on processing emotional vocalizations provides a clear picture for a bilateral distribution of peak activation (see Fig.…”
Section: The Functional Role Of the Ifc In Processing Emotional Vocalmentioning
confidence: 82%
See 4 more Smart Citations
“…These results together suggest that both the left and the right IFC are involved in the processing of emotional value from voices with no clear laterality effects (Kotz et al, 2003). Summarizing the peak activations across all fMRI and PET studies on processing emotional vocalizations provides a clear picture for a bilateral distribution of peak activation (see Fig.…”
Section: The Functional Role Of the Ifc In Processing Emotional Vocalmentioning
confidence: 82%
“…Recent neuroimaging studies found several right IFC peak activations distributed from the posterior to the anterior IFC located in BA 44 Kotz et al, 2003), BA 45 (Bach et al, 2008;Beaucousin et al, 2007;Ethofer et al, 2006;Sander et al, 2005), and BA 47 (Bach et al, 2008;Beaucousin et al, 2007;Belin et al, 2008a;Ethofer et al, 2009;Mitchell, 2006;Sander et al, 2005), as well as in the fOP Kotz et al, 2003;Mitchell et al, 2003;Schirmer et al, 2004) (see Fig. 2).…”
Section: The Functional Role Of the Ifc In Processing Emotional Vocalmentioning
confidence: 92%
See 3 more Smart Citations